A flame retardant and degradable PP decorative film and preparation method thereof

By using the hot pressing forming technology of the flame retardant matrix layer and the flame retardant protective layer in the polypropylene decorative film, the synergistic effect of hydrotalcite and antioxidant is used to solve the flammability problem of polypropylene decorative film, and the flame retardancy and resistance are achieved Improved temperature.

CN118952802BActive Publication Date: 2025-02-25ZHEJIANG JINSHENG DEOCRATION MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411440422.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-25
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing polypropylene decorative films are flammable in the air due to their low oxygen index, resulting in limited application range.

Method used

The flame retardant matrix layer and the flame retardant protective layer are used to form a PP decorative film with an integrated structure. The flame retardant protective layer uses hydrotalcite as the flame retardant material and works in concert with the antioxidant to improve the stability of polypropylene.

Benefits of technology

The flame retardancy and temperature resistance of PP decorative film are realized, while the stability of polypropylene is improved, and the flammability problem of polypropylene decorative film is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of decorative films, and specifically relates to a flame-retardant and degradable PP decorative film and a preparation method thereof, wherein the flame-retardant and degradable PP decorative film comprises: a flame-retardant base layer and a flame-retardant protective layer located on the surface of the flame-retardant base layer, and the flame-retardant base layer contains a degradable material, and the flame-retardant protective layer contains hydrotalcite, and provides a formula of the flame-retardant base layer and the flame-retardant protective layer, as well as a preparation method of the flame-retardant and degradable PP decorative film. The present invention solves the flame-retardant defects of existing polypropylene decorative films, and utilizes a flame-retardant base layer and a flame-retardant protective layer, both of which have flame-retardant functions, to obtain an integrated PP decorative film, and the flame-retardant protective layer uses hydrotalcite as a flame-retardant material, which not only has an overall flame-retardant effect and temperature resistance, but also can absorb free radicals and form a synergistic effect with antioxidants to ensure the stability of polypropylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of decorative films, and in particular relates to a flame-retardant and degradable PP decorative film and a preparation method thereof. Background Art

[0002] With the development of technology and the continuous improvement of living standards, people's requirements for decoration materials are constantly increasing, from the original simple and practical to environmental protection, beauty, comfort and other aspects. Among them, decorative film is currently a more commonly used indoor decoration material, generally including polyvinyl chloride decorative film, polyethylene decorative film, polypropylene decorative film and polyester decorative film. This type of decorative film has the advantages of excellent wear resistance and corrosion resistance, good insulation, etc., and is widely used in furniture, floors, wooden doors, walls and other fields.

[0003] Polypropylene decorative film has the advantages of environmental protection and processability, and can replace polyvinyl chloride decorative film to a certain extent, becoming a truly environmentally friendly decorative film. However, polypropylene decorative film is a hydrocarbon polymer material with a low oxygen index and is flammable in the air, which limits its application range. Summary of the invention

[0004] In view of the problems in the prior art, the present invention provides a flame retardant and degradable PP decorative film, which solves the flame retardancy defects of the existing polypropylene decorative film, and obtains a PP decorative film with an integrated structure by hot pressing a flame retardant base layer and a flame retardant protective layer, both of which have flame retardant functions. The flame retardant protective layer uses hydrotalcite as a flame retardant material, which not only has an overall flame retardant effect and temperature resistance, but also can absorb free radicals and form a synergistic effect with antioxidants to ensure the stability of polypropylene.

[0005] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0006] A flame retardant and degradable PP decorative film comprises: a flame retardant base layer and a flame retardant protective layer located on the surface of the flame retardant base layer, wherein the flame retardant base layer contains degradable materials. The thickness of the flame retardant base layer is 50-80 μm, and the thickness of the flame retardant protective layer is 10-20 μm.

[0007] The mass ratio of the flame retardant base layer is: 100 parts of polypropylene resin, 5-10 parts of antistatic agent, 10-20 parts of barrier agent, 3-5 parts of flame retardant, 10-15 parts of degradable agent and 15-20 parts of filler.

[0008] The polypropylene resin is mixed with a random copolymer PP resin and a block copolymer PP resin, and the mass ratio of the random copolymer PP resin to the block copolymer PP resin is 2-3:3, the ethylene content of the random copolymer PP resin is 10%-30%; the ethylene content of the block copolymer PP resin is 10%-30%. The random copolymer PP resin and the block copolymer PP resin are compounded to obtain a PP resin with the advantages of high strength, high rigidity, good heat resistance, good dimensional stability, good processing performance and excellent low-temperature toughness.

[0009] The antistatic agent is made of polyvinyl alcohol condensation polymer powder. The polypropylene film has good electrical insulation and high resistivity. Static electricity will be generated during friction, shearing, impact and the like. The high insulation of the polypropylene film itself causes static electricity to accumulate continuously and cannot be leaked, resulting in the adhesion of dust and particles. In order to solve the problem of static electricity accumulation, polyvinyl alcohol condensation polymer has conjugated double bonds, which can realize the migration of electrons within and between molecules, thereby realizing the migration of static electricity electrons; the polyvinyl alcohol condensation polymer containing conjugated double bonds is added to the polypropylene film and homogeneously dispersed throughout the polypropylene resin, thereby improving the insulation of the polypropylene film and realizing the transfer of static electricity charges; the polypropylene alcohol condensation polymer is obtained by using polypropylene alcohol as the raw material and then fragmenting after high-temperature polycondensation. The preparation method of the polypropylene alcohol condensation polymer powder includes the following steps: a1, adding polyvinyl alcohol to distilled water and stirring at a constant temperature to form a The polyvinyl alcohol is dissolved in distilled water and the dissolution rate of the polyvinyl alcohol is increased by constant temperature stirring, thereby obtaining a homogeneous solution with a certain temperature; a2, spraying the homogeneous solution into a reactor, and purging at a constant temperature to obtain dry polyvinyl alcohol particles, the spraying amount is 3-7mL / min, and the spraying area is 100-300cm 2, the temperature is 120-140℃, the constant temperature purging adopts dry nitrogen at 110-120℃, and the purging speed is 10-15mL / min; this step disperses the dissolved polyvinyl alcohol into particles by spraying, and dries the polyvinyl alcohol at the temperature in the reactor. During the nitrogen purging process, the atmosphere containing water vapor is replaced by dry nitrogen, which effectively solves the water absorption problem of polyvinyl alcohol and ensures the drying of polyvinyl alcohol particles; a3, spraying the polyvinyl alcohol particles into a high-temperature reactor, and obtaining polyvinyl alcohol condensation polymer particles after constant temperature sedimentation, the blowing speed is 5-10g / min, the temperature of constant temperature sedimentation is 255-265℃, and the sedimentation time is 0.5-1h. This step utilizes the granularity of the dry polyvinyl alcohol particles themselves and performs high-temperature sedimentation in a high-temperature reactor. In this process, the polyvinyl alcohol particles The polycondensation under heat forms a polymer containing conjugated double bonds, namely, a polyvinyl alcohol condensation product, and the polycondensation process is an in-situ condensation process of the polyvinyl alcohol particles, while the particles themselves are still kept, so the polyvinyl alcohol condensation product remains granular; a4, the polyvinyl alcohol condensation particles are put into ether for blending, and the polyvinyl alcohol condensation particles are dried after low-temperature grinding to obtain polyethanol condensation fine powder, wherein the mass ratio of the polyvinyl alcohol condensation particles to the ether is 5-9:1, the temperature of the low-temperature grinding is 5-10°C, the grinding pressure is 0.5-0.7MPa, and the drying temperature is 50-70°C; this step utilizes the insolubility of the polyvinyl alcohol condensation particles in the ether and the permeability of the ether itself, and can penetrate into the gaps in the polyvinyl alcohol condensation particles, and form gap fractures during the low-temperature extrusion process, thereby further refining the polyvinyl alcohol condensation particles to obtain polyvinyl alcohol condensation fine powder. The polyvinyl alcohol condensation polymer fine powder uses polyvinyl alcohol as the initial raw material, and the polyvinyl alcohol is finely divided by spray drying, and an in-situ polycondensation reaction is formed under the action of temperature to obtain fine polyvinyl alcohol condensation polymer; on this basis, the polyvinyl alcohol condensation polymer particles are further finely divided by low-temperature grinding, thereby obtaining the polyvinyl alcohol condensation polymer fine powder. The polyvinyl alcohol condensation polymer in fine powder state has good fluidity and dispersibility, can be uniformly dispersed in the entire flame retardant matrix layer, and form an antistatic network system, which effectively solves the problem of static electricity accumulation.

[0010] The flame retardant is melamine cyanurate, which is a salt synthesized from melamine and cyanuric acid and belongs to nitrogen flame retardant. The melamine cyanurate will decompose under heat, and the decomposition process will absorb a large amount of heat in the flame retardant matrix layer, thereby reducing the surface temperature of the flame retardant collective layer and slowing down the combustion speed, thereby achieving the effect of temperature control and flame retardancy; as the combustion progresses, melamine and cyanuric acid further decompose into non-combustible gas, forming a dilution barrier layer in the matrix layer, reducing the combustible substances and oxygen in the polymer, and also preventing the convection of heat and oxygen, thereby achieving the flame retardant effect.

[0011] The barrier agent adopts porous silicon oxygen material, which uses silicon oxygen bond as the main connection structure, has good mechanical stability and temperature resistance, and the bond energy of silicon oxygen bond is relatively large, which is a stable binding force between silicon and oxygen atoms, and can still maintain the integrity of the structure under high temperature or oxidizing environment. At the same time, the electronegativity difference of silicon oxygen atoms is large, which will show a certain electrostatic attraction effect, and play the role of assisting the antistatic network system; therefore, the porous silicon oxygen structure can not only utilize its own silicon oxygen bond effect to improve the overall heat resistance and weather resistance, but also the porous structure's own permeation system ensures that the barrier agent forms a physical clamping structure in the entire barrier matrix; the porous silicon oxygen material in the barrier agent is obtained by silicon hydroxyl condensation reaction, and while showing a good hydroxyl active structure, the pores formed by itself in the condensation reaction The invention can play a barrier effect and achieve the purpose of protecting the flame retardant substrate layer. The preparation method of the barrier agent comprises the following steps: b1, adding propyltrichlorosilane, isopropyltrichlorosilane and ethyltrichlorosilane into ether and stirring for 20-30 minutes, spraying and standing for 20-30 minutes after concentration, and sintering to obtain silicon oxide core particles, wherein the mass ratio of propyltrichlorosilane, isopropyltrichlorosilane and ethyltrichlorosilane is 3-4:2-3:1, the mass ratio of ethyltrichlorosilane to ether is 1:15-20, the stirring speed is 300-500r / min, the concentration temperature is 40-45°C, the volume after concentration is 35-45% of the original volume of ether, the spraying speed of the spraying is 3-5mL / min, and the area is 100-200cm 2, the atmosphere in which the spray is allowed to stand is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, and the sintering temperature is 200-230°C; this step uses ether as a solvent to form a homogeneous dispersion of ethyltrichlorosilane, propyltrichlorosilane and isopropyltrichlorosilane, and forms in-situ hydrolysis and sintering polycondensation in the spray droplets, thereby obtaining composite silicon oxygen core particles formed by the polycondensation of ethyltrihydroxysilane, propyltrihydroxysilane and isopropyltrihydroxysilane, the core particles not only contain gas-barrier mesoporous structure particles, but also contain short side chains of propyl, isopropyl and ethyl, and silanol active groups on the mesoporous structure particles; b2, dodecyltrichlorosilane and ethyl cellulose are added to ether and stirred evenly to form a dissolved liquid, then putting the silicon oxide core particles into the dissolving liquid for ultrasonication for 20-30 minutes, filtering and drying and then standing for 20-30 minutes to obtain hydrolyzed coated silicon oxide particles, the mass ratio of dodecyl trichlorosilane to ethyl cellulose is 1:3-5, and the concentration of ethyl cellulose in ether is 50-90g / L, the stirring speed is 300-500r / min, the mass ratio of the silicon oxide core particles to the dissolving liquid is 1:5-10, the temperature of the ultrasonication is 5-10°C, the ultrasonic frequency is 80-90kHz, the temperature of the filtration and drying is 40-45°C, the temperature of the standing is 5-10°C, the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 7-9:1, and this step utilizes ethyl cellulose The solubility of cellulose and dodecyltrichlorosilane in ether forms a homogeneous dispersed dilute solution, and the silicon oxide core particles are dispersed in the entire solution by ultrasound, and the ethyl, propyl and isopropyl groups are kept open. During the filtering and drying process, dodecyltrichlorosilane and ethyl cellulose form a stable coating on the surface of the silicon oxide core particles, and the ethyl, propyl and isopropyl groups penetrate into the ethyl cellulose, ensuring the stability of the liquid film; during the standing process, the water vapor in the standing atmosphere will gradually penetrate into the coating and convert dodecyltrichlorosilane into dodecyltrihydroxysilane, and the hydrolysis reaction belongs to the hydrolysis reaction of the coating layer; b3, the hydrolyzed coated silicon oxide particles are allowed to stand for 20-40 minutes, and then placed in ethanol for ultrasonication for 0.5-1 hour , drying to obtain porous silicon oxide particles, which are the barrier agent, the standing temperature is 110-120°C, the mass ratio of the hydrolyzed coated silicon oxide particles to ethanol is 1:5-8, the ultrasonic frequency is 80-100kHz, and the temperature is 10-20°C; the drying temperature is 120-150°C; this step utilizes the standing method to promote the in-situ hydrolysis of the hydrolysis product in the coating layer, ensure the condensation of the hydroxyl groups in dodecyl trihydroxy silane, and the connection reaction between dodecyl trihydroxy and the core; during the ultrasonic treatment, the ethyl cellulose in the hydrolyzed coated silicon oxide particles is dissolved by ethanol, thereby realizing the porosity of the coating layer. At the same time, the ultrasound can also completely disperse the short side chains of ethyl, propyl and isopropyl in the silicon oxide core, and completely open the dodecyl group.The barrier prepared by this process has a mesoporous silicon oxide material as the core and a porous dodecylsilane coating as the surface porous layer. The core is rich in hydroxyl activity and has exposed short side chains represented by ethyl, isopropyl and propyl and long side chains represented by dodecyl. Therefore, the barrier forms a chemical connection of surface hydroxyls in the flame retardant matrix layer, and there is also a physical clamping effect of the dodecylsilane coating layer. The physical friction of ethyl, propyl and isopropyl and the long-chain stretching structure of dodecylsilane greatly improve the fixation of the material.

[0012] The degradable agent is polylactic acid or carbonate.

[0013] The filler is calcium carbonate.

[0014] The mass ratio of the flame retardant protective layer is: 80-90 parts of polypropylene, 5-10 parts of polyvinyl alcohol, 10-12 parts of hydrotalcite, and 5-12 parts of antioxidant.

[0015] The hydrotalcite is aluminum-magnesium hydrotalcite, which is an anionic layered compound with a special layered structure, consisting of a main layer plate with a positive charge and anions inserted between the layers. 2+ and Al 3+ These positive charges are formed through OH - The Mg on the layered plate 2+ Can be surrounded by Al with similar radius within a certain range 3+ Isomorphous substitution makes the main layer plate have a permanent positive charge; the middle layer has exchangeable anions such as CO3 2- , the negative charge it carries is balanced with the positive charge on the layer plate, making the structure electrically neutral. At the same time, there is some crystal water in the remaining space between the layers. In the flame retardant system, hydrotalcite releases a large amount of water and carbon dioxide when it is thermally decomposed, and absorbs a large amount of heat, which can reduce the temperature of the combustion system. The water vapor and carbon dioxide gas released during the decomposition process can dilute and block the combustible gas. The magnesium aluminum oxide generated by thermal decomposition and the carbide formed when the polymer material is burned form a protective film on the surface of the material, blocking the further invasion of oxygen and playing a flame retardant effect; at the same time, the water molecules between the hydrotalcite layers can be formed and released at low temperatures, which not only achieves the purpose of diluting the combustible gas, but also isolates oxygen, absorbs heat, and reduces the high temperature generated. Hydrotalcite and polyvinyl alcohol can form a barrier system to achieve excellent oxygen isolation effect and reduce oxygen penetration oxidation.

[0016] The antioxidant is a hindered phenol antioxidant, specifically 2,6-di-tert-butyl-4-methylphenol or antioxidant 1010. The hindered phenol antioxidant provides hydrogen atoms through the steric hindrance effect in its molecular structure and the phenolic hydroxyl group, destroys the free radical reaction of polypropylene degradation, and generates hydroperoxides and aromatic oxygen free radicals, thereby reducing the activity of free radicals, thereby inhibiting chain reactions and protecting polypropylene from oxidation. The antioxidant and hydrotalcite form free radical transfer, adsorption and consumption, which can ensure the stability of polypropylene in the flame retardant protective layer under light environment.

[0017] The preparation method of the PP decorative film comprises the following steps:

[0018] Step 1, respectively putting the raw materials of the flame retardant base layer and the flame retardant protective layer into different stirring tubes and stirring them evenly to obtain a flame retardant base mixture and a flame retardant protective mixture;

[0019] Step 2, melt-extrude the flame-retardant matrix mixture to obtain a flame-retardant matrix layer, and then blend and extrude the flame-retardant protective mixture to obtain a flame-retardant protective layer;

[0020] Step 3, covering the flame retardant protective layer on the flame retardant base layer, and obtaining a flame retardant and degradable PP decorative film after hot pressing, wherein the temperature of the hot pressing is 130-150°C and the pressure is 0.3-0.5MPa. This step uses the polypropylene contained in the flame retardant protective layer and the flame retardant base layer as the basis to form a permeable bonding, thereby ensuring the integrated structure of the PP decorative film.

[0021] It can be seen from the above description that the present invention has the following advantages:

[0022] 1. The present invention solves the flame retardancy defects of the existing polypropylene decorative film, and obtains an integrated PP decorative film by hot-pressing a flame retardant base layer and a flame retardant protective layer, both of which have flame retardant functions. The flame retardant protective layer uses hydrotalcite as a flame retardant material, which not only has an overall flame retardant effect and temperature resistance, but also can absorb free radicals and form a synergistic effect with antioxidants to ensure the stability of polypropylene.

[0023] 2. The present invention utilizes polyvinyl alcohol condensation polymer as an antistatic agent to form charge adsorption, realize the migration of electrostatic electrons, and improve the insulation of the polypropylene base layer. At the same time, the hydrotalcite in the flame retardant protective layer also has a certain electrostatic adsorption effect, which controls the static electricity between layers and reduces the influence of static electricity on polypropylene. That is, the antistatic effect of the PP decorative film is achieved through the combined action of polyvinyl alcohol condensation polymer and hydrotalcite.

[0024] 3. The present invention uses porous silicon oxide material as a barrier agent, and cooperates with its own mesoporous structure and polyvinyl alcohol condensation product to form a gas barrier effect. At the same time, the layered structure of hydrotalcite can play an oxygen barrier effect, that is, a multi-layer barrier structure with porous silicon oxide material-polyvinyl alcohol condensation product and hydrotalcite as the theme is established in the entire PP decorative film. DETAILED DESCRIPTION

[0025] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.

[0026] Example 1

[0027] A flame retardant and degradable PP decorative film comprises: a flame retardant base layer and a flame retardant protective layer located on the surface of the flame retardant base layer, wherein the flame retardant base layer contains degradable materials. The thickness of the flame retardant base layer is 50 μm, and the thickness of the flame retardant protective layer is 10 μm.

[0028] The mass ratio of the flame retardant substrate layer is: 100 parts of polypropylene resin, 5 parts of antistatic agent, 10 parts of barrier agent, 3 parts of flame retardant, 10 parts of degradable agent and 15 parts of filler.

[0029] The polypropylene resin is mixed with a random copolymer PP resin and a block copolymer PP resin, and the mass ratio of the random copolymer PP resin to the block copolymer PP resin is 2:3. The ethylene content in the random copolymer PP resin is 10%; the ethylene content in the block copolymer PP resin is 10%.

[0030] The antistatic agent is a polyvinyl alcohol condensation polymer powder, and the preparation method of the polyvinyl alcohol condensation polymer powder comprises the following steps: a1, adding polyvinyl alcohol to distilled water and stirring at a constant temperature to form a homogeneous solution; the concentration of the polyvinyl alcohol in the distilled water is 600g / L, the stirring speed of the constant temperature stirring is 500r / min, and the temperature is 80°C; a2, spraying the homogeneous solution into a reaction kettle, and blowing at a constant temperature to obtain dry polyvinyl alcohol particles, the spraying amount is 3mL / min, and the spraying area is 100cm 2 , the temperature is 120℃, the constant temperature purging adopts dry nitrogen at 110℃, and the purging speed is 10mL / min; a3, the polyvinyl alcohol particles are sprayed into the high temperature reaction kettle, and the polyvinyl alcohol condensation polymer particles are obtained after constant temperature sedimentation, the blowing speed is 5g / min, the constant temperature sedimentation temperature is 255℃, and the sedimentation time is 0.5h; a4, the polyvinyl alcohol condensation polymer particles are put into ether for blending, and the polyethanol condensation polymer powder is obtained after low temperature grinding and drying, the mass ratio of the polyvinyl alcohol condensation polymer particles to the ether is 5:1, the temperature of the low temperature grinding is 5℃, the grinding pressure is 0.5MPa, and the drying temperature is 50℃.

[0031] The flame retardant is melamine cyanurate.

[0032] The barrier agent adopts porous silicon oxide material. Specifically, the barrier agent uses mesoporous silicon oxide material as the core, and porous dodecyl silane coating as the surface porous layer. The core is rich in hydroxyl activity and exposes short side chains represented by ethyl, isopropyl and propyl and long side chains represented by dodecyl. The preparation method of the barrier agent includes the following steps: b1, adding propyl trichlorosilane, isopropyl trichlorosilane and ethyl trichlorosilane into ether and stirring for 20 minutes. After concentrating, spraying and standing for 20 minutes, sintering to obtain silicon oxide core particles. The mass ratio of propyl trichlorosilane, isopropyl trichlorosilane and ethyl trichlorosilane is 3:2:1, the mass ratio of ethyl trichlorosilane to ether is 1:15, the stirring speed is 300 r / min, the concentration temperature is 40°C, the volume after concentration is 35% of the original volume of ether, the spraying speed of the spray standing is 3 mL / min, and the area is 100 cm 2 , the spray is allowed to stand in a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, and the sintering temperature is 200°C; b2, dodecyltrichlorosilane and ethyl cellulose are added to ether and stirred evenly to form a dissolving solution, and then the silicon oxide core particles are placed in the dissolving solution for ultrasonication for 20 minutes, filtered and dried, and then allowed to stand for 20 minutes to obtain hydrolyzed coated silicon oxide particles, the mass ratio of dodecyltrichlorosilane to ethyl cellulose is 1:3, and the concentration of ethyl cellulose in ether is 50g / L, the stirring speed is 300r / min, the silicon oxide core particles and the dissolving solution are stirred at 300r / min, and the silicon oxide core particles are stirred at 300r / min. The mass ratio of the liquid is 1:5, the temperature of the ultrasound is 5°C, the frequency of the ultrasound is 80kHz, the temperature of the filtration and drying is 40°C, the temperature of the standing is 5°C, the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 7:1; b3, the hydrolyzed coated silicon oxide particles are allowed to stand for 20 minutes, and then placed in ethanol for ultrasound for 0.5 hours, and dried to obtain porous silicon oxide particles, which are the barrier agent, the standing temperature is 110°C, the mass ratio of the hydrolyzed coated silicon oxide particles to ethanol is 1:5, the frequency of the ultrasound is 80kHz, and the temperature is 10°C; the drying temperature is 120°C.

[0033] The degradable agent is polylactic acid.

[0034] The filler is calcium carbonate.

[0035] The mass ratio of the flame retardant protective layer is: 80 parts of polypropylene, 5 parts of polyvinyl alcohol, 10 parts of hydrotalcite, and 5 parts of antioxidant.

[0036] The hydrotalcite is aluminum-magnesium hydrotalcite.

[0037] The antioxidant is 2,6-di-tert-butyl-4-methylphenol.

[0038] The preparation method of the PP decorative film comprises the following steps:

[0039] Step 1, respectively putting the raw materials of the flame retardant base layer and the flame retardant protective layer into different stirring tubes and stirring them evenly to obtain a flame retardant base mixture and a flame retardant protective mixture;

[0040] Step 2, melt-extrude the flame-retardant matrix mixture to obtain a flame-retardant matrix layer, and then blend and extrude the flame-retardant protective mixture to obtain a flame-retardant protective layer;

[0041] Step 3, covering the flame retardant protective layer on the flame retardant base layer, and obtaining a flame retardant and degradable PP decorative film after hot pressing and laminating, wherein the temperature of the hot pressing and laminating is 130° C. and the pressure is 0.3 MPa.

[0042] Example 2

[0043] A flame retardant and degradable PP decorative film comprises: a flame retardant base layer and a flame retardant protective layer located on the surface of the flame retardant base layer, wherein the flame retardant base layer contains degradable materials. The thickness of the flame retardant base layer is 80 μm, and the thickness of the flame retardant protective layer is 20 μm.

[0044] The mass ratio of the flame retardant substrate layer is: 100 parts of polypropylene resin, 10 parts of antistatic agent, 20 parts of barrier agent, 5 parts of flame retardant, 15 parts of degradable agent and 20 parts of filler.

[0045] The polypropylene resin is mixed with a random copolymer PP resin and a block copolymer PP resin, and the mass ratio of the random copolymer PP resin to the block copolymer PP resin is 3:3. The ethylene content in the random copolymer PP resin is 30%; the ethylene content in the block copolymer PP resin is 30%.

[0046] The antistatic agent is a polyvinyl alcohol condensation polymer powder, and the preparation method of the polyvinyl alcohol condensation polymer powder comprises the following steps: a1, adding polyvinyl alcohol to distilled water and stirring at a constant temperature to form a homogeneous solution; the concentration of the polyvinyl alcohol in the distilled water is 800g / L, the stirring speed of the constant temperature stirring is 800r / min, and the temperature is 90°C; a2, spraying the homogeneous solution into a reaction kettle, and blowing at a constant temperature to obtain dry polyvinyl alcohol particles, the spraying amount is 7mL / min, and the spraying area is 300cm 2, the temperature is 140℃, the constant temperature purging adopts dry nitrogen at 120℃, and the purging speed is 15mL / min; a3, the polyvinyl alcohol particles are sprayed into a high temperature reaction kettle, and polyvinyl alcohol condensation polymer particles are obtained after constant temperature sedimentation, the blowing speed is 10g / min, the constant temperature sedimentation temperature is 265℃, and the sedimentation time is 1h; a4, the polyvinyl alcohol condensation polymer particles are put into ether for blending, and the polyvinyl alcohol condensation polymer powder is obtained after low temperature grinding and drying, the mass ratio of the polyvinyl alcohol condensation polymer particles to the ether is 9:1, the temperature of the low temperature grinding is 10℃, the grinding pressure is 0.7MPa, and the drying temperature is 70℃.

[0047] The flame retardant is melamine cyanurate.

[0048] The barrier agent adopts porous silicon oxide material. Specifically, the barrier agent uses mesoporous silicon oxide material as the core, and porous dodecyl silane coating as the surface porous layer. The core is rich in hydroxyl activity and exposes short side chains represented by ethyl, isopropyl and propyl and long side chains represented by dodecyl. The preparation method of the barrier agent includes the following steps: b1, adding propyl trichlorosilane, isopropyl trichlorosilane and ethyl trichlorosilane into ether and stirring for 30 minutes. After concentrating, spraying and standing for 30 minutes, sintering to obtain silicon oxide core particles. The mass ratio of propyl trichlorosilane, isopropyl trichlorosilane and ethyl trichlorosilane is 4:3:1, the mass ratio of ethyl trichlorosilane to ether is 1:20, the stirring speed is 500r / min, the concentration temperature is 45°C, the volume after concentration is 45% of the original volume of ether, the spraying speed of the spray standing is 5mL / min, and the area is 200cm 2, the spray is allowed to stand in a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1, and the sintering temperature is 230°C; b2, dodecyltrichlorosilane and ethyl cellulose are added to ether and stirred evenly to form a dissolving solution, and then the silicon oxide core particles are placed in the dissolving solution for ultrasonication for 30 minutes, filtered and dried, and then allowed to stand for 30 minutes to obtain hydrolyzed coated silicon oxide particles, the mass ratio of dodecyltrichlorosilane to ethyl cellulose is 1:5, and the concentration of ethyl cellulose in ether is 90g / L, the stirring speed is 500r / min, and the silicon oxide core particles and the dissolving solution are stirred at 500r / min. The mass ratio of the above-mentioned particles is 1:10, the temperature of the ultrasound is 10°C, the frequency of the ultrasound is 90kHz, the temperature of the filtration and drying is 45°C, the temperature of the standing state is 10°C, the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9:1; b3, the hydrolyzed coated silicon oxide particles are allowed to stand for 40 minutes, and then placed in ethanol for ultrasound for 1 hour, and dried to obtain porous silicon oxide particles, which are the barrier agent, the standing temperature is 120°C, the mass ratio of the hydrolyzed coated silicon oxide particles to ethanol is 1:8, the frequency of the ultrasound is 100kHz, and the temperature is 20°C; the drying temperature is 150°C.

[0049] The degradable agent is carbonate.

[0050] The filler is calcium carbonate.

[0051] The mass ratio of the flame retardant protective layer is: 90 parts of polypropylene, 10 parts of polyvinyl alcohol, 12 parts of hydrotalcite, and 12 parts of antioxidant.

[0052] The hydrotalcite is aluminum-magnesium hydrotalcite.

[0053] The antioxidant is antioxidant 1010.

[0054] The preparation method of the PP decorative film comprises the following steps:

[0055] Step 1, respectively putting the raw materials of the flame retardant base layer and the flame retardant protective layer into different stirring tubes and stirring them evenly to obtain a flame retardant base mixture and a flame retardant protective mixture;

[0056] Step 2, melt-extrude the flame-retardant matrix mixture to obtain a flame-retardant matrix layer, and then blend and extrude the flame-retardant protective mixture to obtain a flame-retardant protective layer;

[0057] Step 3, covering the flame retardant protective layer on the flame retardant base layer, and obtaining a flame retardant and degradable PP decorative film after hot pressing and laminating, wherein the temperature of the hot pressing and laminating is 150° C. and the pressure is 0.5 MPa.

[0058] Example 3

[0059] A flame retardant and degradable PP decorative film comprises: a flame retardant base layer and a flame retardant protective layer located on the surface of the flame retardant base layer, wherein the flame retardant base layer contains degradable materials. The thickness of the flame retardant base layer is 70 μm, and the thickness of the flame retardant protective layer is 15 μm.

[0060] The mass ratio of the flame retardant substrate layer is: 100 parts of polypropylene resin, 8 parts of antistatic agent, 15 parts of barrier agent, 4 parts of flame retardant, 13 parts of degradable agent and 18 parts of filler.

[0061] The polypropylene resin is mixed with a random copolymer PP resin and a block copolymer PP resin, and the mass ratio of the random copolymer PP resin to the block copolymer PP resin is 2:3. The ethylene content in the random copolymer PP resin is 20%; the ethylene content in the block copolymer PP resin is 20%.

[0062] The antistatic agent is a polyvinyl alcohol condensation polymer powder, and the preparation method of the polyvinyl alcohol condensation polymer powder comprises the following steps: a1, adding polyvinyl alcohol to distilled water and stirring at a constant temperature to form a homogeneous solution; the concentration of the polyvinyl alcohol in the distilled water is 700g / L, the stirring speed of the constant temperature stirring is 700r / min, and the temperature is 85°C; a2, spraying the homogeneous solution into a reaction kettle, and blowing at a constant temperature to obtain dry polyvinyl alcohol particles, the spraying amount is 5mL / min, and the spraying area is 200cm 2 , the temperature is 130℃, the constant temperature purging adopts dry nitrogen at 115℃, and the purging speed is 12mL / min; a3, the polyvinyl alcohol particles are sprayed into a high temperature reaction kettle, and polyvinyl alcohol condensation polymer particles are obtained after constant temperature sedimentation, the blowing speed is 8g / min, the constant temperature sedimentation temperature is 260℃, and the sedimentation time is 1h; a4, the polyvinyl alcohol condensation polymer particles are put into ether for blending, and the polyvinyl alcohol condensation polymer powder is obtained after low temperature grinding and drying, the mass ratio of the polyvinyl alcohol condensation polymer particles to the ether is 7:1, the temperature of the low temperature grinding is 8℃, the grinding pressure is 0.6MPa, and the drying temperature is 60℃.

[0063] The flame retardant is melamine cyanurate.

[0064] The barrier agent adopts porous silicon oxide material. Specifically, the barrier agent uses mesoporous silicon oxide material as the core, and porous dodecyl silane coating as the surface porous layer. The core is rich in hydroxyl activity and exposes short side chains represented by ethyl, isopropyl and propyl and long side chains represented by dodecyl. The preparation method of the barrier agent includes the following steps: b1, adding propyl trichlorosilane, isopropyl trichlorosilane and ethyl trichlorosilane into ether and stirring for 25 minutes. After concentrating, spraying and standing for 25 minutes, sintering to obtain silicon oxide core particles. The mass ratio of propyl trichlorosilane, isopropyl trichlorosilane and ethyl trichlorosilane is 4:2:1, the mass ratio of ethyl trichlorosilane to ether is 1:18, the stirring speed is 400r / min, the concentration temperature is 43°C, the volume after concentration is 40% of the original volume of ether, the spraying speed of the spray standing is 4mL / min, and the area is 150cm 2 b2, adding dodecyltrichlorosilane and ethyl cellulose into ether and stirring evenly to form a solution, then putting the silicon oxide core particles into the solution and ultrasonicating for 25 minutes, filtering and drying, and then standing for 25 minutes to obtain hydrolyzed coated silicon oxide particles, wherein the mass ratio of dodecyltrichlorosilane to ethyl cellulose is 1:4, and the concentration of ethyl cellulose in ether is 80g / L, the stirring speed is 400r / min, and the silicon oxide core particles and the solution are stirred at 400r / min. The mass ratio of the hydrolyzed silicon oxide particles is 1:8, the temperature of the ultrasound is 8°C, the frequency of the ultrasound is 85kHz, the temperature of the filtration and drying is 43°C, the temperature of the standing temperature is 8°C, the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1; b3, the hydrolyzed coated silicon oxide particles are allowed to stand for 30 minutes, then placed in ethanol for ultrasound for 1 hour, and dried to obtain porous silicon oxide particles, which are the barrier agent, the standing temperature is 115°C, the mass ratio of the hydrolyzed coated silicon oxide particles to ethanol is 1:7, the frequency of the ultrasound is 90kHz, and the temperature is 15°C; the drying temperature is 140°C.

[0065] The degradable agent is polylactic acid.

[0066] The filler is calcium carbonate.

[0067] The mass ratio of the flame retardant protective layer is: 85 parts of polypropylene, 8 parts of polyvinyl alcohol, 11 parts of hydrotalcite, and 9 parts of antioxidant.

[0068] The hydrotalcite is aluminum-magnesium hydrotalcite.

[0069] The antioxidant is 2,6-di-tert-butyl-4-methylphenol.

[0070] The preparation method of the PP decorative film comprises the following steps:

[0071] Step 1, respectively putting the raw materials of the flame retardant base layer and the flame retardant protective layer into different stirring tubes and stirring them evenly to obtain a flame retardant base mixture and a flame retardant protective mixture;

[0072] Step 2, melt-extrude the flame-retardant matrix mixture to obtain a flame-retardant matrix layer, and then blend and extrude the flame-retardant protective mixture to obtain a flame-retardant protective layer;

[0073] Step 3, covering the flame retardant protective layer on the flame retardant base layer, and obtaining a flame retardant and degradable PP decorative film after hot pressing and laminating, wherein the temperature of the hot pressing and laminating is 140° C. and the pressure is 0.4 MPa.

[0074] Example 4

[0075] A flame retardant and degradable PP decorative film comprises: a flame retardant base layer and a flame retardant protective layer located on the surface of the flame retardant base layer, wherein the flame retardant base layer contains degradable materials. The thickness of the flame retardant base layer is 70 μm, and the thickness of the flame retardant protective layer is 15 μm.

[0076] The mass ratio of the flame retardant substrate layer is: 100 parts of polypropylene resin, 8 parts of antistatic agent, 15 parts of barrier agent, 4 parts of flame retardant, 13 parts of degradable agent and 18 parts of filler.

[0077] The polypropylene resin is mixed with a random copolymer PP resin and a block copolymer PP resin, and the mass ratio of the random copolymer PP resin to the block copolymer PP resin is 2:3. The ethylene content in the random copolymer PP resin is 20%; the ethylene content in the block copolymer PP resin is 20%.

[0078] The antistatic agent is a polyvinyl alcohol condensation polymer powder, and the preparation method of the polyvinyl alcohol condensation polymer powder comprises the following steps: a1, adding polyvinyl alcohol to distilled water and stirring at a constant temperature to form a homogeneous solution; the concentration of the polyvinyl alcohol in the distilled water is 700g / L, the stirring speed of the constant temperature stirring is 700r / min, and the temperature is 85°C; a2, spraying the homogeneous solution into a reaction kettle, and blowing at a constant temperature to obtain dry polyvinyl alcohol particles, the spraying amount is 5mL / min, and the spraying area is 200cm 2, the temperature is 130℃, the constant temperature purging adopts dry nitrogen at 115℃, and the purging speed is 12mL / min; a3, the polyvinyl alcohol particles are sprayed into a high temperature reaction kettle, and polyvinyl alcohol condensation polymer particles are obtained after constant temperature sedimentation, the blowing speed is 8g / min, the constant temperature sedimentation temperature is 260℃, and the sedimentation time is 1h; a4, the polyvinyl alcohol condensation polymer particles are put into ether for blending, and the polyvinyl alcohol condensation polymer powder is obtained after low temperature grinding and drying, the mass ratio of the polyvinyl alcohol condensation polymer particles to the ether is 7:1, the temperature of the low temperature grinding is 8℃, the grinding pressure is 0.6MPa, and the drying temperature is 60℃.

[0079] The flame retardant is melamine cyanurate.

[0080] The barrier agent is nano silicon dioxide particles, and the particle size of the nano silicon dioxide particles is 300-800nm.

[0081] The degradable agent is polylactic acid.

[0082] The filler is calcium carbonate.

[0083] The mass ratio of the flame retardant protective layer is: 85 parts of polypropylene, 8 parts of polyvinyl alcohol, 11 parts of hydrotalcite, and 9 parts of antioxidant.

[0084] The hydrotalcite is aluminum-magnesium hydrotalcite.

[0085] The antioxidant is 2,6-di-tert-butyl-4-methylphenol.

[0086] The preparation method of the PP decorative film comprises the following steps:

[0087] Step 1, respectively putting the raw materials of the flame retardant base layer and the flame retardant protective layer into different stirring tubes and stirring them evenly to obtain a flame retardant base mixture and a flame retardant protective mixture;

[0088] Step 2, melt-extrude the flame-retardant matrix mixture to obtain a flame-retardant matrix layer, and then blend and extrude the flame-retardant protective mixture to obtain a flame-retardant protective layer;

[0089] Step 3, covering the flame retardant protective layer on the flame retardant base layer, and obtaining a flame retardant and degradable PP decorative film after hot pressing and laminating, wherein the temperature of the hot pressing and laminating is 140° C. and the pressure is 0.4 MPa.

[0090] Example 5

[0091] A flame retardant and degradable PP decorative film comprises: a flame retardant base layer and a flame retardant protective layer located on the surface of the flame retardant base layer, wherein the flame retardant base layer contains degradable materials. The thickness of the flame retardant base layer is 70 μm, and the thickness of the flame retardant protective layer is 15 μm.

[0092] The mass ratio of the flame retardant substrate layer is: 100 parts of polypropylene resin, 8 parts of antistatic agent, 15 parts of barrier agent, 4 parts of flame retardant, 13 parts of degradable agent and 18 parts of filler.

[0093] The polypropylene resin is mixed with a random copolymer PP resin and a block copolymer PP resin, and the mass ratio of the random copolymer PP resin to the block copolymer PP resin is 2:3. The ethylene content in the random copolymer PP resin is 20%; the ethylene content in the block copolymer PP resin is 20%.

[0094] The antistatic agent is bis(β-hydroxyethyl) coconut amine.

[0095] The flame retardant is melamine cyanurate.

[0096] The barrier agent is nano silicon dioxide particles, and the particle size of the nano silicon dioxide particles is 300-800nm.

[0097] The degradable agent is polylactic acid.

[0098] The filler is calcium carbonate.

[0099] The mass ratio of the flame retardant protective layer is: 85 parts of polypropylene, 8 parts of polyvinyl alcohol, 11 parts of hydrotalcite, and 9 parts of antioxidant.

[0100] The hydrotalcite is aluminum-magnesium hydrotalcite.

[0101] The antioxidant is 2,6-di-tert-butyl-4-methylphenol.

[0102] The preparation method of the PP decorative film comprises the following steps:

[0103] Step 1, respectively putting the raw materials of the flame retardant base layer and the flame retardant protective layer into different stirring tubes and stirring them evenly to obtain a flame retardant base mixture and a flame retardant protective mixture;

[0104] Step 2, melt-extrude the flame-retardant matrix mixture to obtain a flame-retardant matrix layer, and then blend and extrude the flame-retardant protective mixture to obtain a flame-retardant protective layer;

[0105] Step 3, covering the flame retardant protective layer on the flame retardant base layer, and obtaining a flame retardant and degradable PP decorative film after hot pressing and laminating, wherein the temperature of the hot pressing and laminating is 140° C. and the pressure is 0.4 MPa.

[0106] Comparative Example 1

[0107] The difference between Comparative Example 1 and Example 5 is that Comparative Example 1 does not contain a degradable agent.

[0108] Performance Testing

[0109] The performance tests were conducted using the polypropylene decorative films of Examples 1-5 and Comparative Example 1 as samples, and the results are as follows:

[0110]

[0111] The degradation condition is that the PP decorative film is buried in soil with a temperature of 32-38° C. and a relative humidity of 90-100%; the ultraviolet aging is performed by irradiating the film for 3000 hours according to the method of national standard 16422.3.

[0112] The above shows that the PP decoration prepared by the present technical solution has good combustion performance and mechanical strength, and its degradation performance is significantly improved.

[0113] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A flame retardant and degradable PP decorative film, characterized in that: include: A flame retardant base layer and a flame retardant protective layer located on the surface of the flame retardant base layer, wherein the flame retardant base layer contains a degradable material, and the flame retardant protective layer contains hydrotalcite; The thickness of the flame retardant substrate layer is 50-80 μm, and the thickness of the flame retardant protective layer is 10-20 μm; The mass ratio of the flame retardant substrate layer is: 100 parts of polypropylene resin, 5-10 parts of antistatic agent, 10-20 parts of barrier agent, 3-5 parts of flame retardant, 10-15 parts of degradable agent, and 15-20 parts of filler; the polypropylene resin is mixed with random copolymer PP resin and block copolymer PP resin, and the mass ratio of random copolymer PP resin to block copolymer PP resin is 2-3:3, the ethylene content in the random copolymer PP resin is 10%-30%; the ethylene content in the block copolymer PP resin is 10%-30%; The barrier agent adopts porous silicon oxide material, and the barrier agent has a mesoporous silicon oxide material as the core, a porous dodecylsilane coating as the surface porous layer, and the core is rich in hydroxyl activity, and has exposed short side chains represented by ethyl, isopropyl and propyl groups and long side chains represented by dodecyl groups; The preparation method of the barrier agent comprises the following steps: b1, adding propyltrichlorosilane, isopropyltrichlorosilane and ethyltrichlorosilane to diethyl ether and stirring for 20-30 minutes, spraying and standing for 20-30 minutes after concentration, and sintering to obtain silicon-oxygen core particles; b2, adding dodecyltrichlorosilane and ethyl cellulose into ether and stirring evenly to form a dissolving solution, then placing the silicon oxide core particles into the dissolving solution and ultrasonicating for 20-30 minutes, filtering and drying, and then standing for 20-30 minutes to obtain hydrolyzed coated silicon oxide particles; b3, let the hydrolyzed coated silicon oxide particles stand for 20-40 minutes, then put them into ethanol for ultrasonic treatment for 0.5-1 hour, and dry them to obtain porous silicon oxide particles, which are the barrier agent.

2. The flame retardant and degradable PP decorative film according to claim 1, characterized in that: The antistatic agent is polyvinyl alcohol polycondensate fine powder; the flame retardant is melamine cyanurate.

3. The flame retardant and degradable PP decorative film according to claim 1, characterized in that: The degradable agent is polylactic acid or carbonate; the filler is calcium carbonate.

4. The flame retardant and degradable PP decorative film according to claim 1, characterized in that: The mass ratio of the flame retardant protective layer is: 80-90 parts of polypropylene, 5-10 parts of polyvinyl alcohol, 10-12 parts of hydrotalcite, and 5-12 parts of antioxidant.

5. The flame retardant and degradable PP decorative film according to claim 4, characterized in that: The hydrotalcite is aluminum-magnesium hydrotalcite; the antioxidant is a hindered phenol antioxidant, specifically 2,6-di-tert-butyl-4-methylphenol or antioxidant 1010.

6. The flame retardant and degradable PP decorative film according to claim 1, characterized in that: The preparation method of the PP decorative film comprises the following steps: Step 1, respectively putting the raw materials of the flame retardant base layer and the flame retardant protective layer into different stirring tubes and stirring them evenly to obtain a flame retardant base mixture and a flame retardant protective mixture; Step 2, melt-extrude the flame-retardant matrix mixture to obtain a flame-retardant matrix layer, and then blend and extrude the flame-retardant protective mixture to obtain a flame-retardant protective layer; Step 3, covering the flame retardant protective layer on the flame retardant base layer, and obtaining a flame retardant and degradable PP decorative film after hot pressing and laminating, wherein the temperature of the hot pressing and laminating is 130-150° C. and the pressure is 0.3-0.5 MPa.

Citation Information

Patent Citations

  • Efficient and environmentally friendly flame retardant polypropylene compound

    CN109251408A

  • Flame-retardant and degradable PP decorative film and preparation method thereof

    CN114106469A